Impact of analyst recommendations on stock returns: Evidence from the German stock market - Michael Souček; Thomas Wasserek (European University Viadrina, Department of Business Administration and Economics, 2014)
The purpose of this article is to examine the impact of analysts' recommendation downgrades, upgrades, and reiterations on German stock returns and as to whether prof- itable investment strategies could potentially be designed around these recommendations. The paper provides a unique detailed descriptive analysis of financial analysts' recommendations changes on German stock market over the last decade. First, we show that changes in recommendations yield significant positive (negative) abnormal gross returns for upgrades (downgrades), respectively. Reiterations, on the other hand, do not cause statistically significant stock market reactions. We show, that stock price reactions following recommendation revisions are strongest at the announcement day and last up to six months for upgrades and four month for downgrades. A bulk of market reactions, appears on the recommendation event date and shortly before so that investors must trade in a timely manner to profit from analyst recommendations. A one-day delayed reaction to the change in recommendations do not allow for significant abnormal returns for most of the recommendation shifts.
Keywords: 330; Asset Pricing; Analyst Recommendations; Efficient Market Hypothesis; Abnormal Returns